O rito da unção: sucessos e fracassos de uma modalidade de cura religiosa na Igreja Adventista do Sétimo Dia - Torres, Tania Maria Lopes (2018)
This research set out to qualitatively investigate the success or failure of the anointing of the sick as a means of statistically altering the predictable natural history of a disease. Its methodology consisted of an outcome study, as proposed by Finkler (1985), aimed at a rural community, in the Lagoa Bonita district, in Engenheiro Coelho, Brazil, where most of the residents profess Seventh-Day Adventistism. The data were collected by means of semistructured interviews with twenty-two participants. The sample was formed either with respondents (90% of whom were Adventists) who underwent the ritual of anointing (referred to as “subjects”) or, in case they were not available, with respondents who met the two ad hoc criteria for inclusion (referred to as “informants”): (1) close kinship; and (2) being present during the ministration of the rite. At least 14 (i.e., 63%) of the subjects could be described as being in severe or terminal condition. For the analysis of the data, Bardin’s content analysis method was used. At the end of the investigation, it was confirmed that the anointing of the sick is sociologically effective and anthropologically justifiable, since it belongs to the dimension of symbolic regulation, which is why spiritual caregivers can minister to patients with chronic pain in aspects often neglected by biomedicine, hence the need for its institutionalization as a possibility of treatment